Explorations in AR: Finding Its Value - de Sá Ribeiro, Mauricio Gomes; Lafuente Mazuecos, Isabel; Marinho, Fabiano; Neves Gomes dos Santos, Alice (Virtual, Augmented and Mixed Reality. Multimodal Interaction, 2019)
This paper presents the main findings regarding the overall effectiveness of an AR-based wearable device for different types of users performing basic, common tasks throughout a few demo scenarios, thus identifying opportunities for improvement and further investment. A series of user tests were carried out among participants using this head-mounted prototype while different aspects of their interaction and overall experience were evaluated. It was given special attention to desirability factors, as well as pain points and obstacles to completing the different scenarios. This paper presents main insights regarding several features for an ideal head-mounted AR experience to the user, as well as their view regarding the future of digital media consumption. It also discusses some limitations and lessons learned for future work. Our results allow us to shed light onto the scope of expectations of potential end users, in order to help in the design and engineering of these devices. We argue that the value of exploratory studies of such as these lies in its potential to delve into innovative paths and their potential implications, otherwise difficult to trace.